Outcome of young children with high‐grade glioma treated with irradiation‐avoiding intensive chemotherapy regimens: Final report of the Head Start II and III trials. Issue 10 (22nd June 2016) - Espinoza, Juan C; Haley, Kelley; Patel, Neha; Dhall, Girish; Gardner, Sharon; Allen, Jeffrey; Torkildson, Joseph; Cornelius, Albert; Rassekh, Rod; Bedros, Antranik; Etzl, Morris; Garvin, James; et al.
Abstract: Purpose: To report the final analysis of survival outcomes for children with newly diagnosed high‐grade glioma (HGG) treated on the "Head Start" (HS) II and III protocols with chemotherapy and intent to avoid irradiation in children <6 years old. Patients and Methods: Between 1997 and 2009, 32 eligible children were enrolled in HS II and III with anaplastic astrocytoma (AA, n = 19), glioblastoma multiforme (GBM, n = 11), or other HGG (n = 2). Central pathology review was completed on 78% of patients. Patients with predominantly brainstem tumors were excluded. Patients were to be treated with single induction chemotherapy regimen C, comprising four cycles of vincristine, carboplatin, and temozolomide. Following induction, patients underwent marrow‐ablative chemotherapy and autologous hematopoietic cell rescue. Irradiation was used for patients with residual tumor after consolidation or >6 years old or at the time of tumor progression. Results: The 5‐year event‐free survival (EFS) and overall survival (OS) for all HGG patients were 25 ± 8% and 36 ± 9%, respectively. The EFS at 5 years for patients with AA and GBM were 24 ± 11% and 30 ± 16%, respectively ( P = 0.65). The OS at 5 years for patients with AA and GBM was 34 ± 12% and 35 ± 16%, respectively ( P = 0.83). Children <36 months old experienced improved 5‐year EFS and OS of 44 ± 17% and 63 ± 17%, compared with children 36–71 months old (31 ± 13% and 38 ± 14%) and children >72 months old (0% and 13 ± 12%). Conclusions: Irradiation‐avoiding treatment strategies should be evaluated further in young children with HGG given similar survival rates to older children receiving standard irradiation‐containing therapies.